Pengelompokkan Foraminifera Bentik Di Perairan Teluk Balikpapan Berdasarkan Komposisi Pembentuk Cangkang - Widianingsih, Mastuti (Journal of Marine and Aquatic Sciences; Vol 3 No 1 (2017)DO - 10.24843/jmas.2017.v3.i01.1-9, 2017)
Balikpapan Bay is one of the bays in Indonesia. One of the organisms in these waters are benthic foraminifera. The objective of this research was to determine the type of benthic foraminifera based composition forming the shells in Balikpapan Bay, East Kalimantan. The sediment samples were taken at a depth of 0-20 meters, then do picking, collection, as well as the identification of the type and composition shells forming of the benthic foraminifera. The results showed the benthic foraminifera Balikpapan Bay waters with sediment samples at a depth of 0-20 meters consists of benthic foraminifera shell of sandy, benthic foraminifera shell of porcelain, and benthic foraminifera shell of hyalin .
Keywords: foraminifera, shell, Balikpapan bay